B-mode and Doppler features of struma ovarii - Royo, P.; Alcazar, J. L.; Virgen, Margarita; Mazaira, J.; Jurado, M.; Lopez, G. (My University, 2007)
Mature teratomas are relatively common ovarian tumors that exhibit a variable sonographic appearance, due to their heterogeneous histological components1. Caspi et al. proposed some pathognomonic echo patterns for the sonographic diagnosis of this tumor2. The agreement between these pathognomonic echo patterns and postoperative histological diagnosis has been reported to be as high as 97.45%2. Struma ovarii are rare ovarian tumors, considered as variants of mature teratomas, in which more than 50% of the neoplastic tissue is generally thyroid tissue3. Little has been reported on the sonographic appearance of this tumor4. We therefore reviewed clinical and sonographic data on a series of histologically confirmed cases of struma ovarii (n = 9) and mature teratoma (n = 120) surgically removed at our institution over the last 10 years, in order to determine whether there were any differences in their morphological and vascular ultrasound patterns. © Ultrasound in Obstetrics and Gynecology